Feeding ecology and niche segregation of the spider crab Libinia ferreirae (Decapoda, Brachyura, Majoidea), a symbiont of Lychnorhiza lucerna (Cnidaria, Scyphozoa, Rhizostomeae) - Lemos Goncalves, Geslaine Rafaela [UNESP]; Negreiros-Fransozo, Maria Lucia [UNESP]; Fransozo, Adilson [UNESP]; Castilho, Antonio Leao [UNESP] (Springer, 2019)
Feeding strategies provide essential information to help understand symbiotic relationships and resource competition as well as environmental integrity. This study examined the feeding ecology of the spider crab Libinia ferreirae, which is commonly associated with the jellyfish Lychnorhiza lucerna during part of its life cycle, especially the juvenile stage. In the adult phase, the crab is a host for many epibionts that live on its carapace. The crabs were collected in 1 year, and the stomach contents were analyzed by the percentage points and the frequency of occurrence of the food items. We identified ten food items (food in the advanced stage of digestion was unidentifiable) and microplastic particles in the gastric contents of the crabs. The food items with high abundances were sediment, crustaceans, and cnidarians. We found niche partitioning of the spider crab's diet during the benthic (free-living) and planktonic (L. lucerna association) phases. The fact that microplastic is part of the diet of L. ferreirae is concerning and shows how environmental contamination with plastic material has been incorporated into the marine food chain as a whole.
Keywords: Frequency of occurrence; Percentage points; Association; Microplastic; Host